2013
DOI: 10.1128/aac.02023-12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacogenetic Markers ofCYP2B6, Clinical Factors, and Drug-Drug Interaction on Efavirenz Concentrations in HIV/Tuberculosis-Coinfected Patients

Abstract: bComprehensive information on the effects of cytochrome P450 2B6 (CYP2B6) polymorphisms, clinical factors, and drug-drug interactions on efavirenz concentrations in HIV/tuberculosis-coinfected (HIV/TB) patients is unavailable. A total of 139 HIV/TB adults, 101 of whom received a rifampin-containing anti-TB regimen, were prospectively enrolled to receive efavirenz (600 mg)/ tenofovir/lamivudine. Nine single nucleotide polymorphisms (SNPs) within CYP2B6 were genotyped. Plasma efavirenz concentrations were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 27 publications
5
30
1
Order By: Relevance
“…Ten studies, had proportions for both on and off RH, with nine reporting higher proportions of patients with EFV < 1000 ng ml –1 during RH coadministration than without RH, although the difference was highly variable, ranging between 1.1 and 21.1%. Only two studies, one in Thai patients and one in South Africans , reported a lower proportion of patients with EFV < 1000 ng ml –1 during RH coadministration than without RH, with a difference <5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies, had proportions for both on and off RH, with nine reporting higher proportions of patients with EFV < 1000 ng ml –1 during RH coadministration than without RH, although the difference was highly variable, ranging between 1.1 and 21.1%. Only two studies, one in Thai patients and one in South Africans , reported a lower proportion of patients with EFV < 1000 ng ml –1 during RH coadministration than without RH, with a difference <5%.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted among adult patients in Tanzania and Thailand or in children in South Africa highlight within country variability with regard to effect of RH on EFV concentrations , which could partially be explained by the small sample size, or differences in methodology used and the pharmacogenetics within different ethnic groups. As highlighted in the review by Colic et al .…”
Section: Discussionmentioning
confidence: 99%
“…31) In fact, there are multiple factors that could contribute to affect plasma efavirenz concentration, including gender, age, body weight, liver and renal impairment. 32) Thus, this study was also designed to investigate the various interactions of host genetics with clinical parameters and efavirenz concentration by univariate and multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a prospective open-label trial to evaluate the frequency of CYP2B6 single nucleotide polymorphisms (SNPs) and haplotypes in 139 adult Thai patients coinfected with HIV and tuberculosis at the Bamrasnaradura Infectious Diseases Institute, Ministry of Public Health, Nonthaburi, Thailand (16). The institutional ethics committees of the Bam-rasnaradura Infectious Diseases Institute and the Thai Ministry of Public Health approved the study.…”
Section: Methodsmentioning
confidence: 99%